Application of System Approach for Design and Operation of Process Control Systems in Oil and Gas Industry - Hai, Le Xuan; Hai, Vo Viet (ASEAN Journal of Chemical Engineering, 2017)
Process Control Systems are essential parts in oil and gas production plants. The design and operations of these systems are really complex because they must comply with stringent technical requirements, as well as safety and environmental regulations from authorities and third party certifying agents. In order to simplify and systemize the design and operation, in this study, we have built a logical Flow Chart of System Approach and applied it for study and performing the relevant works for Process Control Systems.